Fear of Missing Out (FoMO) dan Keputusan Pembelian Generasi Z di Era Media Sosial - Rizky Khairunnisa; Melian Elsa Putri; Ranggau Faroza Putra; Eko Hadi Saputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The phenomenon of Fear of Missing Out (FoMO) has emerged as a significant psychosocial factor influencing the consumption behavior of Generation Z in the social media era. This study aims to explore how FoMO shapes the purchasing decisions of Generation Z using a qualitative approach, focusing on subjective experiences, digital social pressures, and interactions with viral content. A descriptive-interpretative qualitative method was employed, collecting data through in-depth interviews and observations of social media activity among Generation Z respondents actively engaged in digital platforms. Thematic analysis was applied to identify patterns of FoMO experiences and their impact on purchasing decisions. Findings reveal that FoMO arises from the need for social connection, social comparison with peers and influencers, and intensive exposure to digital trends. This phenomenon drives consumptive behaviors, particularly impulsive purchases, influenced by social validation and emotional impulses. Generation Z’s purchasing decisions are contextual, multidimensional, and not entirely rational, yet meaningful within the framework of digital social identity. The study underscores the necessity of a qualitative approach to comprehensively understand the psychological, social, and cultural complexities of FoMO and consumer behavior. The results provide a conceptual foundation for ethical and relevant marketing strategies targeting young consumers in the digital era.